Tensile Performance, Lap-Splice Length and Behavior of Concretes Confined by Prefabricated C-FRCM System - Donguk Choi; Sorrasak Vachirapanyakun; Munckhtuvshin Ochirbud; Undram Naidangjav; Sangsu Ha; Youngho Kim (International Journal of Concrete Structures and Materials, 2021)
Abstract Results of an experimental study aimed to evaluate tensile performance, lap-splice length of carbon fabric-reinforced cementitious matrix system (C-FRCM), and performance of concretes confined by C-FRCM are presented. Green high-strength mortar was used in this study which actively utilized recycled fine aggregate and fine waste glass powder to partially substitute cementitious binder. Test plans were developed in due consideration of prefabricated C-FRCM for strengthening concrete columns: 14 tensile tests, 12 lap-splice tests, and 6 uniaxial compression tests of plain concrete specimens confined by C-FRCM were performed. Test variable for the tensile test was number of fabric layers (one or two layers). Nominal strength of the C-FRCM with two fabric layers was 11.0 MPa while it was 7.4 MPa with one fabric layer in tension. Full strength of the carbon fabric was developed in all tensile tests while the C-FRCM with two fabric layers (with axial fiber amount = 0.59% by vol.) showed pseudo-ductile behavior. From the lap-splice tests in direct tension, an increased lap-splice length was required for the double fabrics over that for the single fabrics. The required splice length was about 170 mm for the single fabrics and it was about 310 mm for the double fabrics. Plain concrete cylinders and prismatic specimens were laterally confined by C-FRCM and subjected to uniaxial compression. All test results showed strain-softening behavior. Compressive strength increased by 10–41% while ductility also increased by 6–45% indicating applicability of the prefabricated type C-FRCM in the future.